DECENTRALIZATION AND GOVERNANCE: CASE STUDIES FROM DEVELOPING COUNTRIES - Urfi Yousuf; Jan Mohammad Bhat (RADJA PUBLIKA, 2024)
Decentralization, the process of redistributing or dispersing functions, powers, people, or things away from a central location or authority, has been a significant reform in governance structures across developing countries. This paper examines the theoretical underpinnings of decentralization and its implications for governance, drawing on case studies from various developing countries. The analysis focuses on the political, administrative, and fiscal dimensions of decentralization and evaluates its impact on democratic governance, service delivery, and local accountability.